QUR'ANI CUES TO NURTURE AN EARLY READING CULTURE: (AN EXAMINATION OF THE EDUCATIONAL VALUE OF QS. AL-ALAQ 1-5) - Chandra, Tri Ulva; Marezka Putra, Aldo (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
One of the causes of backwardness in Muslim-majority countries including Indonesia is low literacy, Indonesia is ranked at the bottom in terms of literacy levels. This condition is suspected due to the neglect of literacy education from an early age by families and educational institutions. Meanwhile, the Qur'an as a guide to life for Muslims has echoed literacy even since the Qur'an was first revealed, this is stated in QS. Al-'Alaq [96]: 1-5. This paper aims to elaborate the content of the Qur'an in QS. Al-'Alaq [96]: 1-5 as an appropriate and effective conceptual solution in promoting an early reading culture. This research is qualitative, with a form of library research with an analytical descriptive presentation. The results of this study show that the Qur'an, which is the solution to various problems of human life, provides instructions to increase children's interest in reading which must start from childhood as the first commandment. With one of the preventive measures in the form of read aloud techniques as indicated by the process of revelation Jibril repeats the words of Allah to Muhammad, besides the repetition of the command to read in QS. Al-'Alaq [96]: 1-5 also gives a strong impression of the importance of interest and reading culture. Reading is also claimed to be the first step in opening the horizons of knowledge from an early age.